Response of Black Locust (Robinia pseudacacia Linn.) to Phosphorus and Modybdenum Application under Nursery Conditions - Verma, K. S.; Sharma, Kamal; Joshi, N. K. (Indian Forester, 1990)
Growth and biomass production of black locust have been observed to be increased significanlly at 30 kg P2O5 ha-1 Mo application did not cause any significant variation in growth parameters, However biomoss production increased significantly upto 40g Mo ha-1. 30 kg phosphorus and 40g molybdenum per hectare applied together showed the maximum and significant increase in growth and biomass production.